Strategi City Branding Provinsi Bengkulu Melalui Festival Tabot - Ramahwati Saputri; Welly Wirman (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Bengkulu Province is an area rich in culture and traditions which are still considered a legacy from our ancestors, one of which is Tabot. That in this era of globalization, competition between regions is getting tougher by increasingly developing regional potential and uniqueness so that they are able to compete with other regions. In this case, a city needs a strategy to create a strong regional or global positioning, this is better known as City Branding. City branding is one of the appropriate strategies to be implemented by the Bengkulu Province Tourism Office to develop a city identity that can attract domestic and foreign tourists to visit Bengkulu Province. This research aims to understand the city branding strategy of the Bengkulu Province Tourism Office in developing city branding through the Tabot Festival. This research method uses a qualitative research method using a descriptive approach. This qualitative research aims to explain the phenomenon through interview, observation and documentation data collection techniques. In this research there were five informants who were taken using purposive techniques. In data analysis techniques by reducing data, presenting data, and drawing conclusions. And checking the validity of the data was carried out using triangulation. The results of this research are for an identity strategy to first determine the identity of the city which can differentiate it from other areas which is symbolized using a logo or tagline. The objective strategy for city branding through the Tabot festival is to raise the image of the city and to attract the interest of local and foreign tourists. The strategy used by the Bengkulu Province Tourism Office is to collaborate with stakeholders related to the tourism sector such as the tourism industry, and to promote through media such as electronic media, online media, printed promotional media such as billboards and banners. The coherence strategy is to have a common message conveyed in promoting this branding, namely through communication carried out with other stakeholders by including the branding logo from Bengkulu Province.